Environmental Impacts of Pasture-Basedfarming - McDowell, Richard W (CABI, 2014)
At the heart of this book reside the tensions that people face when managing grazed ecosystems throughout the world. Sustaining the natural capital of our grazed lands is crucial, as these areas represent a very large part of our global terrestrial ecosystems. This challenge is grounded in the socio-economic expectations of land users and nations. The biophysical elements that need to be managed will vary, depending on the ecosystem involved. For rangelands, the maintenance of perennial vegetations cover is critical from a soil erosion perspective. For more intensive grasslands, the emission of nutrients and gases is of great concern. But in all cases, the connections between land, water and air are becoming increasingly evident.